Mutual contaminants relational realization and photocatalytic treatment using Cu2MgSnS4 decorated BaTiO3. (March 2020) - Ali, Ahsan; Liang, Yongping; Ahmed, Shehzad; Yang, Bian; Guo, Baolin; Yang, Yaodong
Graphical abstract: Highlights: Enhanced carrier generation was grasped by carefully selecting P-type absorber material as a co-catalyst with ferroelectric BTO. The space charge layer at interface and controlled loading of CMTS with different ratios decreased the bandgap. MCRR concluded that organic dyes have a high influence on bacterial growth. The growth cycles increased in the presence of organic contaminants. CMTS-BTO showed 97% percent removal of organic dyes within five minutes and inactivated a considerable amount of bacterium. Abstract: Emerging contaminants and related health risks restrain aged treatment approaches. A better-premise understanding of water remediation attained by mutual contamination relational realization (MCRR). Precisely engineered Cu2 MgSnS4 (CMTS) decorated BaTiO3 (BTO) composites demonstrated a remarkable removal of organic contaminants and inactivation of harmful bacterium. It showed a valuable 97 % degradation of organic dyes and strong bacterial antagonism for both Escherichia coli and Staphylococcus aureus . Implantation of P-type CMTS on the surface of n-type BTO caused formation of a space charge layer (SCL), which affected diffusion of charge carriers. Junction at the interface of constituent materials and built-in electric field increased negative and positive carrier's separation. Bandgap of the composites decreased from 3.4 eV to 2.6 eV by adjusting the composition of CMTS, which drastically augmented their ability to harvest the visible light. Therefore this study opens a new door for potential photocatalytic applications.